2014
DOI: 10.2147/ppa.s42789
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of agomelatine in the treatment of depression

Abstract: Depression is a severe and usually recurrent mental disorder which often leads to a significant impairment of everyday functioning, a reduced quality of life, and also great suffering of the patients. The treatment of a depressive disorder is not only limited to acute treatment; it also requires prolonged management. Patient compliance is of utmost importance. Unpleasant adverse effects and their impact on everyday living often lead to a premature discontinuation of antidepressant treatment and result in an un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 56 publications
(144 reference statements)
0
20
0
2
Order By: Relevance
“…Agomelatine and escitalopram were suggested as favorable balanced antidepressants which may be explained based on their pharmacological profiles. Agomelatine, combining norepinephrine and dopamine disinhibition (NDDI) plus melatonergic agonism [44], has a favorable adverse effect profile mostly due to the fact that it does not affect sexual functioning, weight gain, or metabolic syndrome, and positively regulates sleep quality [45,46]. The balance benefit observed in the present analysis for agomelatine is thus due to its relatively good tolerability and not due to superior efficacy.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Agomelatine and escitalopram were suggested as favorable balanced antidepressants which may be explained based on their pharmacological profiles. Agomelatine, combining norepinephrine and dopamine disinhibition (NDDI) plus melatonergic agonism [44], has a favorable adverse effect profile mostly due to the fact that it does not affect sexual functioning, weight gain, or metabolic syndrome, and positively regulates sleep quality [45,46]. The balance benefit observed in the present analysis for agomelatine is thus due to its relatively good tolerability and not due to superior efficacy.…”
Section: Discussionmentioning
confidence: 79%
“…Interaction effects were restricted to be not doubly nonlinear with products involving nonlinear effects on both covariates not included in the model. The RCS model was assessed using 3 knots based on combinations out of 7 possible knot locations for each covariate (dose (mg/day FE ) = [10,20,30,40,50,60,70]; age (years) = [35,40,45,50,55,60,70]), resulting in N = 35 models per covariate. This allowed for a more extensive selection of the optimal knot location compared to Furukawa et al [1], who evaluated only 8 different knot combinations.…”
Section: Bayesian Models For Nmamentioning
confidence: 99%
See 1 more Smart Citation
“…3,21,22) In Caucasians, the interindividual variability of the AUC after the oral administration of agomelatine varied in different reports (100-150% CV).…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of new drug targets or mechanisms of action for treating depression has attracted much attention as many patients are unresponsive to the available antidepressants and have difficulties in achieving remission. 3) Agomelatine, approved for marketing in the European Union and other countries, 4,5) is an agonist of melatonin MT1 and MT2 receptors and a weak 5-HT2C antagonist, but it has no activity on serotonin, norepinephrine (noradrenaline), or dopamine release. 6,7) A recent meta-analysis has suggested that it causes a greater reduction in symptom scores than the placebo and some other antidepressants; in addition, it has similar efficacy as standard drug treatment for depression.…”
mentioning
confidence: 99%